2000
DOI: 10.1021/la000014i
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Induced Changes of Morphology of J-Aggregates:  Superhelix-to-Tubule Transformation

Abstract: The morphology of the J-aggregates formed after the addition of ionic surfactants into solutions of the 3,3‘-bis(3-carboxypropyl)-5,5‘,6,6‘-tetrachloro-1,1‘-dioctylbenzimidacarbocyanine dye (C8O3) was characterized by absorption and circular dichroism spectroscopy, cryogenic temperature transmission electron microscopy, scanning force microscopy, and small-angle neutron scattering. The optical activity of the C8O3 J-aggregates, existing in aqueous solution as superhelices composed of tubular single strands, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
102
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 41 publications
(53 reference statements)
5
102
0
3
Order By: Relevance
“…[9][10][11][12][13] A number of other porphyrin derivatives, such as TPPS 2 (bi(4-sulfonatophenyl)diphenylporphyrin) and TPPS 3 (tri(4-sulfonatophenyl)phenylporphyrin), 14 TCPP (tetra(4-carboxyphenyl)porphyrin), 15 TPPS 4 (tetra(4-sulfonatophenyl)porphyrin), 16,17 or a mixture of TPPS 4 and SnTPyP (Sn(IV) tetra(4-pyridyl)porphyrin), 18 form aggregates of tubular morphology as well. However, in this paper, we will focus solely on the tubular TPPS 4 aggregates, because of their high stability and reproducibility of their structural and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] A number of other porphyrin derivatives, such as TPPS 2 (bi(4-sulfonatophenyl)diphenylporphyrin) and TPPS 3 (tri(4-sulfonatophenyl)phenylporphyrin), 14 TCPP (tetra(4-carboxyphenyl)porphyrin), 15 TPPS 4 (tetra(4-sulfonatophenyl)porphyrin), 16,17 or a mixture of TPPS 4 and SnTPyP (Sn(IV) tetra(4-pyridyl)porphyrin), 18 form aggregates of tubular morphology as well. However, in this paper, we will focus solely on the tubular TPPS 4 aggregates, because of their high stability and reproducibility of their structural and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Examples of molecules that in solution self-assemble into aggregates of a tubular shape are carbocyanine molecules with hydrophobic and hydrophilic side groups [2][3][4][5][6][7] and porphyrin derivatives. [8][9][10][11][12] Both these molecules yield aggregates with a diameter of the order of 10 nm and a length of up to microns, which explains why they are often referred to as molecular nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…22 This perspective motivates many of the recent studies of the optical absorption and luminescence properties of the collective exciton states in these systems, as well as the energy transport and relaxation caused by these states. [2][3][4][5][6][7][23][24][25][26][27] In homogeneous cylindrical aggregates, the rotational symmetry around the axis imposes strong optical selection rules on the wave number k 2 that characterizes the exciton's Bloch wave function along a ring around the cylinder. In particular, it is easily shown that only states with k 2 = 0 and k 2 = ±1 may carry optical oscillator strength.…”
mentioning
confidence: 99%
“…An interesting example is the case of nanotubular carbocyanine J-aggregates that have recently been developed by Dähne and coworkers 29,30,31 and which have been suggested as building blocks for synthetic light-harvesting systems. These aggregates consist of two walls, which are only a few nanometers apart.…”
Section: Introductionmentioning
confidence: 99%